Structure and transparent conductive properties of F-doped ZnO(FZO) thin films prepared by reactive magnetron sputtering - ZHU Bai-lin; ZHENG Si-long; XIE Ting; WU Jun (Cailiao gongcheng, 2021)
F-doped ZnO (FZO) films were prepared by reactive sputtering using Zn/ZnO/ZnF2 mixture as the target at substrate temperature (Ts) of 150℃ and 300℃ and sputtering atmosphere of Ar+O2 and Ar+H2. The effect of gas flux, Ts, and sputtering atmosphere on the structure and transparent conductive properties of the thin film was investigated. The results show that for FZO films prepared under Ar+O2, Ts=300℃ is conductive to the preparation of films with (002) preferred orientation, high crystallinity, low compressive stress and good transparent conductive properties. For the films prepared under Ar+H2, with the increase of Ts to 300℃, the crystallinity and transmittance of the films improve and the compressive stress reduces, but the film thickness significantly reduces and leads to the deterioration of the conductive properties of the films. The FZO films prepared in the two atmospheres are compared, and it is found that the films prepared in Ar+H2 can obtain better transparent conductive properties (the resistivity of 3.5×10-3 Ω·cm and the average transmittance in visible range of 87%) at 150℃ and in H2 flux range of 0.8-3.2 mL·min-1. The etching effect of H plasma and H doping in the Ar+H2 atmosphere, the bombardment of O ions and the change of oxygen defects of the films in the Ar+O2 atmosphere, the enhancement in reaction activity and mobility of deposited atoms with increasing Ts, and the relationship between Eg and carrier concentration are discussed in detail.